Correlatos da atividade física em pessoas idosas brasileiras : pesquisa nacional de saúde 2019 - Silva, Amanda Santos da (2023)
Physical activity (PA) is influenced by various factors, including intrapersonal, interpersonal/cultural, organizational, physical, and political environmental factors. Recognizing the importance of understanding this phenomenon in different population contexts, this study aimed to identify factors associated with the engagement of PA in Brazilian older adults (i.e., sociodemographic aspects, dietary habits, self-rated health, activities of daily living, non-communicable chronic diseases, mental health, and public policies). This cross-sectional study used data from the National Health Survey conducted in 2019. The sample consisted of 22,726 participants aged 60 years or older, of both sexes, and all data were collected through interviews and questionnaires. Binary logistic regression was used to analyze possible associations between PA and the other investigated factors. Our results showed that men were more active than women (OR = 1.59, 95% CI: 1.40-1.80), and those living in Brazil's northern and northeastern regions were more likely to be inactive compared to the southeastern region. Additionally, individuals with higher education and income (OR = 1.36; 95% CI: 1.06-1.73 and OR = 1.60; 95% CI: 1.22-2.11), with healthy dietary habits (OR = 1.05; 95% CI: 1.03-1.06), with positive self-perceived health (OR = 2.63; 95% CI: 1.49-4.69), with better functional autonomy (OR = 1.22; 95% CI: 1.17-1.27); and those who reported having a nearby public space (such as a square, park, closed street, or beach) for walking, exercising, or engaging in sports had a higher likelihood of being active (OR = 1.49; 95% CI: 1.34-1.67). Therefore, this study concludes that the factors related to weekly engagement in total PA (i.e., 150 min/week) in Brazilian older people included sociodemographic factors, healthy dietary habits, positive health perception, minimal difficulty in activities of daily living and residing near locations where PA is practiced.